Archaeological and Historical Evidence Reveal New Insights on the Maritime Cultural Landscape of the Sea of Galilee - Galili, Ehud (The international journal of nautical archaeology, 2024)
Low water levels of the Sea of Galilee (Lake Kinneret) in recent decades due to droughts and anthropogenic factors have exposed large portions of the lakebed. Archaeological surveys of the newly exposed areas yielded prehistoric sites, harbours, anchorages, shipwrecks, cargoes and shoreline installations, attesting to changing maritime activity on the lake through time. The different assemblages are presented and discussed within the context of the lake’s highly specific physical and climatic settings. Scarcity of shelters, onshore winds and unpredictable lake-level changes influenced human activity, as reflected in the archaeological records. Collectively, the finds represent the history of maritime activity on the Sea of Galilee.